Reinventing Government in Analysis Model of Bureaucracy Service Policy in Indonesia - Nawi, Rusdin; Umar, Zulkarnain (Opción, 2019)
The goal to be achieved is to answer the problems raised from this study, namely: 1) knowing the application of reinventing government in Indonesia; 2) knowing the bureaucratic service policy model in Indonesia; and 3) know- ing reinventing government in the bureaucratic service policy model in Indo- nesia. This type of research is qualitative with the type of case study research related to the bureaucratic service policy of analysis model. Furthrmore, the research informants are parties involved in the service of bureaucracy in In- donesia, both service decision makers in government agencies, state-owned enterprises, private and independent institutions. The data collection tech- niques were in the form of literature review of books, journals, reports on bureaucratic services from updated sources and observed case observations. Data analysis techniques include reduction, presentation and verification of data. The findings of this study are reinventing government in the bureau- cratic service policy model in Indonesia, where the government in running the government must be able to invest in the government to strengthen the exist- ence of the government to serve the public. The bureaucratic service policy model run by government agencies has not combined a variety of general and simple models. The implementation of reinventing government which must be in accordance with the model of “Constructive Bureaucratic Services”, name- ly combining the interests of the state, government, bureaucracy and the pub- lic in one unit “serving” for “service” is the best for the public.